2019
DOI: 10.1111/pbi.13249
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of the Australian wild diploid species Gossypium australe highlights disease resistance and delayed gland morphogenesis

Abstract: Summary The diploid wild cotton species Gossypium australe possesses excellent traits including resistance to disease and delayed gland morphogenesis, and has been successfully used for distant breeding programmes to incorporate disease resistance traits into domesticated cotton. Here, we sequenced the G. australe genome by integrating PacBio, Illumina short read, BioNano (DLS) and Hi‐C technologies, and acquired a high‐quality reference genome with a contig N50 of 1.83 Mb and a scaffold N50 of 143.60 Mb. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 106 publications
(125 reference statements)
6
67
0
Order By: Relevance
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, lots of DEGs were markedly enriched into plant hormone signal transduction pathway. Consistently, it has been reported that auxin [74,75], cytokinins [76,77], ethylene [75,[78][79][80], gibberellin [81], abscisic acid [75,82,83], brassinosteroids [80], salicylic acid [75,78,84], jasmonic acid [75,78,[84][85][86], strigolactones [87] can actively participate in disease response. Among them, salicylic acid signal transduction and jasmonic acid/ethylene signal transduction are considered as the most common plant hormone signal transduction pathways in response to biological or abiotic stress.…”
Section: Discussionsupporting
confidence: 57%
“…Very recently, Udall et al reported the de novo assembly of the genome of G. raimondii and its close relative Gossypium turneri using PacBio long reads, Hi-C, and Bionano optical mapping technologies, which helped to correct some minor assembly errors in previous version of the G. raimondii genome assembly [21]. Using the same strategy, another group published a draft genome of a disease-resistant species Gossypium australe with a contig N50 of 1.83 Mb [22]. In addition, high-resolution transcriptional landscape of G. arboreum is also available [23].…”
Section: Advances In Cotton Genomicsmentioning
confidence: 99%
“…Silencing GauGRAS1 by VIGS leads to glandless stems and petiole and didn't change the form of glands in the leaves in G. australe. Moreover, the gossypol content in the stem of the GauGRAS1silenced plants was signi cantly reduced [38]. However, the molecular mechanism for pigment gland formation remains complicated and unclear, which has limited progress in low-gossypol breeding of cotton.…”
Section: Discussionmentioning
confidence: 99%
“…CGP1 (Cotton Gland Pigmentation 1), which interacted with GoPGF, was identi ed through comparative transcriptome analysis of glanded and glandless cotton accessions and was involved in the regulation of gossypol biosynthesis but not gland formation [36]. In addition, the novel RanBP2 zinc nger protein (ZFP) and GauGRAS1, which played the roles in the development of the cotton gland, were identi ed using suppression subtractive hybridization (SSH) from upland cotton 'Xiangmian 18' [9,[37][38][39]. During the past three decades, there has been some progress in the molecular mechanism of gland formation and the relationship between gossypol and pigment gland.…”
Section: Introductionmentioning
confidence: 99%